Multielement analysis of plant extracts with potential use in the treatment of peptic ulcers by synchrotron radiation total reflection X-ray fluorescence - Vieira,Leticia Diniz; da Silva,Káthia Takeda; Giarola,Rodrigo Sanchez; Inocente,Guilherme Franco; Kushima,Hélio; Hiruma Lima,Clelia Akiko; Hormaza,Joel Mesa (PeerJ, 2018)
Some plants popularly employed for the treatment of peptic ulcers have proved to be attractive sources of new drugs. Despite extensive research, the pharmacological and toxicological potentials of these plants are not fully understood. In this context, the aim of this work was to analyze the multielemental composition of the methanolic extracts of three of those plants, Alchornea glandulosa (AG), Davilla elliptica (DE) and Davilla nitida (DN), with the intention of contributing to the understanding of the mechanisms of action of these extracts. For this purpose, we used the analytical technique of total reflection X-ray fluorescence (TXRF) by synchrotron radiation at the Brazilian Synchrotron Light Source (LNLS/CNPEM). It was possible to determine the concentrations of the elements: P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Rb and Br in all of the samples. Selenium (Se) was detected only in the DN extract. An inverse relationship between the concentrations of elements with proven effectiveness and the gastroprotective activity of extracts considering induction protocols with ethanol and non-steroidal anti-inflammatory drugs (NSAIDs) was obtained. This data suggests that the function of the extract is not only associated with providing the elements for restoring the gastric mucosa but that it also promotes the displacement of these elements from other parts of the mucosa to the damaged area. Correlations between the concentrations of the elements were also obtained. In the DE extract, which is the most effective extract for both induction protocols, the obtained correlations were above 70% among almost all of the elements, and no anticorrelations were found. For the other two extracts, in the less effective extract (AG) anticorrelations above 70% were predominantly found. Meanwhile, in the DN extract, a few high anticorrelations were found, which may explain its intermediate stage of effectiveness.
Keywords: Alchornea glandulosa; Davilla nitida; Davilla elliptica; Synchrotron radiation; Multielement analysis; Plant extracts